2013
DOI: 10.1007/s12639-013-0390-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between excretory/secretory and autoclaved vaccines against RH strain of Toxoplasma gondii in murine models

Abstract: Toxoplasma gondii is an obligate intracellular protozoan that has a major importance in public health, in addition to veterinary medicine. Therefore, the development of an effective vaccine for controlling toxoplasmosis is an important goal. Excretory/secretory antigens (ESA), were previously identified as potential vaccine candidates, proved to play important roles in the pathogenesis and immune escape of the parasite. In addition, autoclaved Toxoplasma vaccine (ATV) is a special type of killed vaccine, recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In light of the fact that T. gondii causes serious public health problems and enormous economic losses, safer and more efficient approaches need to be developed to control this ubiquitous pathogen (Dubey, 2010; Zhu et al, 2017). Previous studies have suggested that DNA vaccines, subunit vaccines, inactivated vaccines and secreted antigens could induce a certain level of humoral and cellular responses and prolong the lifespan of vaccinated mice, but none of these vaccines could provide complete protection against further infection (Innes et al, 2011; Ezz Eldin et al, 2015; Yang et al, 2017; Zheng et al, 2017). Although many researchers have performed a tremendous amount of work to pursue effective drugs and better vaccines, a mature product is unlikely to be available in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the fact that T. gondii causes serious public health problems and enormous economic losses, safer and more efficient approaches need to be developed to control this ubiquitous pathogen (Dubey, 2010; Zhu et al, 2017). Previous studies have suggested that DNA vaccines, subunit vaccines, inactivated vaccines and secreted antigens could induce a certain level of humoral and cellular responses and prolong the lifespan of vaccinated mice, but none of these vaccines could provide complete protection against further infection (Innes et al, 2011; Ezz Eldin et al, 2015; Yang et al, 2017; Zheng et al, 2017). Although many researchers have performed a tremendous amount of work to pursue effective drugs and better vaccines, a mature product is unlikely to be available in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were distributed into seven experimental groups (ten mice per each). T. gondii RH strain infection was induced by intraperitoneal mice injection with 2500 tachyzoites/100 µl saline/ mouse except the healthy controls [Araujo et al1992;Ezz Eldin et al 2015].…”
Section: Experimental Design [Figure 1]mentioning
confidence: 99%
“…The first generation of vaccines contained killed parasites, or native antigens derived from soluble or secretory proteins of cultured tachyzoites. These vaccines only provided limited protection against further infections ( 15 , 16 ). Then when the recombinant DNA technology became available, a variety of subunit vaccines were tried, mainly using surface or secretory proteins such as SAG1 and MIC2 ( 17 – 20 ).…”
Section: Introductionmentioning
confidence: 99%